Market indicators : the best-kept secret to more effective trading and investing - Sipley, Richard, 1966- (Bloomberg Financial., 2009)
"A proprietary trader provides an overview of the most popular market metrics developed and used by professionals. The author synthesizes these market signals and provides a running commentary on why they work, and how to use them to trade better and more profitably"--Provided by publisher.